The life and tragedy of anti-Japanese Korean independence activist Choi Jae-Hyung’s family (based on the records of surviving families members) - Lee, Byong Jo (Journal of Oriental Studies, 2020)
In this article, the author examined the family history of the first Korean naval officer in the Red Army, Choi Pavel Petrovich and his family members, who became victims of the tragic history of the Koreans in the Far East in the modern period. To this end, I mainly used a large number of family history recollections written by Choi Pavel’s surviving families and some of Choi Pavel’s military service-related materials from the Russian State Naval Archives. After graduating from the Frunze Naval School in Leningrad, Choi Pavel became the first Korean officer in the navy of the Soviet Army and traveled all across the seas of the Soviet Union. However, with the death of an older brother during the Civil War and an unexpected death of the father Choi Jae Hyun in 1920, misfortunes began in the Choi family. As naval officer, Choi Pavel also died on October 17, 1938 in Kazakhstan, becoming a victim of the Soviet regime. Around the same time, most of his 10 brothers and sisters, elder and young sisters’ brothers-in-law felt victims of Stalinist repression, and only a few ones managed to escape death. The tragic life story of Choi Pavel’s family symbolizes one aspect in the life of Far East Koreans who became victims of the Soviet regime in the early XXth century. Key words: Choi Jae-Hyung (Choi Pyotr Semyonovich), Choi Pavel, partisan, Stalin’s suppression.